PEMBERDAYAAN USAHA KULINER DI MASA PANDEMI COVID 19 MELALUI MEDIA SOSIAL PADA UKM ALQUDDUS CATERING KARANG REJO RT.03/ RW.03 BANYUMANIK SEMARANG JAWA TENGAH - Nanang Yusroni; Umar Chadhiq; Ratna Kusumawati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
In the current pandemic, many people have lost their jobs, affecting the economy of life. There are so many housewives who have to rack their brains to be able to meet their daily needs. However, LP2M Unwahas collaborated with final semester students to help make a breakthrough to open a catering business for laid-off victims because students and the team have expertise in cooking so they take advantage of the expertise. It became an online catering service. Collaborating with SME Catering under the name Al-Quddus, with an on line system, now it has many customers. The address is on Jl. Karangrejo V/ RT 03/RW 03, Banyumanik, Semarang. With social media is one of the most influential platforms on his business. In addition to promoting its catering, it also has a strategy in its service, namely the menu offered is always different every day. customers can enjoy delicious and healthy meals without leaving the house, because the food will be delivered to their doorstep.